La transformación del mundo rural en la isla de Mallorca durante la Antigüedad tardía (c. 300-902/903 d.c.) - Mas Florit, Catalina, (Limina/limites ;, 2021)
This is the study of the rural landscape of the eastern part of the island of Mallorca (Balearic Islands) during Late Antiquity, providing new data that improves our understanding of one of the least well-known periods of the island. The author describes the results of the study of old archaeological surveys carried out on the island - which had not been published yet - and the results of new archaeological surveys. The conclusions from these studies detected a series of trends that help to better understand the settlement patterns of the island during the transition from the Roman period to medieval times. Furthermore, they help to obtain an overview of different transformations that occurred in the rural world in a territory that was strongly marked by its insularity.